Impact of nocturnal hypoxia on glycaemic control, appetite, gut microbiota and inflammation in adults with type 2 diabetes mellitus: A single‐blind cross‐over trial - Melitta McNarry (The Journal of Physiology, 2024)
High altitude residents have a lower incidence of type 2 diabetes mellitus (T2DM).Therefore, we examined the effect of repeated overnight normobaric hypoxic exposure on glycaemiccontrol, appetite, gut microbiota and inflammation in adults with T2DM. Thirteen adults withT2DM [glycated haemoglobin (HbA1 c ): 61.1 ± 14.1 mmol mol−1 ; aged 64.2 ± 9.4 years; fourfemale] completed a single-blind, randomised, sham-controlled, cross-over study for 10 nights,sleeping when exposed to hypoxia (fractional inspired O2 [FIO 2 ] = 0.155; ∼2500 m simulatedaltitude) or normoxic conditions (FIO 2 = 0.209) in a randomised order. Outcome measures included:fasted plasma [glucose]; [hypoxia inducible factor-1α]; [interleukin-6]; [tumour necrosis factor-α];[interleukin-10]; [heat shock protein 70]; [butyric acid]; peak plasma [glucose] and insulin sensitivityfollowing a 2 h oral glucose tolerance test; body composition; appetite indices ([leptin], [acyl ghrelin],[peptide YY], [glucagon-like peptide-1]); and gut microbiota diversity and abundance [16S rRNAamplicon sequencing]. During intervention periods, accelerometers measured physical activity,sleep duration and efficiency, whereas continuous glucose monitors were used to assess estimatedHbA1c and glucose management indicator and time in target range. Overnight hypoxia was notassociated with changes in any outcome measure (P > 0.05 with small effect sizes) except fastinginsulin sensitivity and gut microbiota alpha diversity, which exhibited trends (P = 0.10; P = 0.08respectively) for a medium beneficial effect (d = 0.49; d = 0.59 respectively). Ten nights of over-night moderate hypoxic exposure did not significantly affect glycaemic control, gut microbiome,appetite, or inflammation in adults with T2DM. However, the intervention was well tolerated anda medium effect-size for improved insulin sensitivity and reduced alpha diversity warrants furtherinvestigation.